Factors Affecting Choice of Comprehensive Motor Insurance in Nepal - Poudel, Aayush; Shrestha, Sujan Raja (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Compared to third party liability insurance, comprehensive motor insurance offers far more coverage. Nevertheless, despite the bigger benefit, owners of motor vehicles are not particularly motivated to purchase comprehensive auto insurance. The purpose of this study is to determine the primary determinants that influence the owners’ choice of auto insurance. Methodology: The study used a descriptive and quantitative research approach to look into how consumers’ choice of automobile insurance is influenced by social, psychological, economic, and vehicle factors. A systematic questionnaire was used to collect data, and it was disseminated both physically and digitally. A total of 247 samples were collected and determined to be useful for the study. Using the Statistical Package for Social Sciences (SPSS), version 26, twelve hypotheses were tested through the use of correlation, multiple regression, and crosstabs (chi-square) analysis in the study of the data. Findings and Conclusion: In addition, the study found that the choice of comprehensive motor insurance was significantly influenced by factors such as marital status, income, age and value of the vehicle, insurance knowledge, and claim history. It also found that psychological and economic factors had a significant impact on this decision. The study’s conclusions showed that people who could afford to pay a large premium, were financially secure, had higher insurance knowledge, and had a favorable claim settlement experience were the main factors influencing their decision to purchase comprehensive auto insurance. Implications: The research was conducted with few variables and there are a lot more variables that might be associated to the choice of motor insurance, as the R square value was only 32.4%. Further variables can be explored and the study can be carried out separately for four wheelers or two wheelers to be more specific. Based on the results, it is recommended that insurance companies focus on educating the public about the insurance coverages, risks, and advantages of having a comprehensive motor insurance, and simultaneously improve the claim service for the loss bearers.